Constructing 3D hierarchical Zn0.2Cd0.8S microspheres for the improved visible-light-driven photocatalytic performance. (6th September 2019) - Yin, Lixiong; Zhang, Feng; Feng, Liangliang; Huang, Jianfeng; Kong, Xingang; Zhang, Haofan; Li, Huimin; Wang, Xiao
Abstract: Nanorod assembled three-dimensional (3D) hierarchical Zn0.2 Cd0.8 S microspheres were successfully prepared by a facile one-pot microwave hydrothermal approach using ethylenediamine (EN) as a template agent. The optimal 3D hierarchical Zn0.2 Cd0.8 S microspheres (ZCS-30) is obtained when adding 30 mL into the synthetic system, which can function as a highly active photocatalyst for H2 evolution under visible-light irradiation with the wavelength of 420 nm, delivering an activity approximately 2.5 and 7.5 times higher than that of Zn0.2 Cd0.8 S nanoparticles and CdS counterparts, respectively, and giving an apparent quantum efficiency (AQE) of 7.4%. Furthermore, the ZCS-30 photocatalyst shows the good stability after the catalytic H2 evolution for 15 h (5 cycles). In addition, the ZCS-30 photocatalyst exhibits the excellent degradation of Rhodamine B (Rh B) almost up to 80% under the visible light irradiation over a period of 150 min. The results demonstrate that ZCS-30 can serve as a promising visible-light-driven bifunctional photocatalyst for water splitting and dye degradation. Graphical abstract: Image 1 Highlights: 3D hierarchical Zn0.2 Cd0.8 S was synthesized by using EN as template agent. ZCS-30 can serve as a promising visible-light-driven bifunctional photocatalysts. ZCS-30 shows a durable stability after catalytic H2 evolution for 15 h (5 cycles).